The effect of levothyroxine treatment in individuals with subclinical hypothyroidism on surrogate markers of atherosclerosis: a meta-analysis of randomized controlled trials. Issue 4 (4th July 2019) - Swaid, Bakr; Kheiri, Babikir; Sundus, Saira; Shah Miran, Muhammad; Haykal, Tarek; Zayed, Yazan; Bachuwa, Ghassan
ABSTRACT: Introduction : Subclinical hypothyroidism is associated with increased carotid intima media thickness (CIMT) and decreased flow-mediated dilation (FMD) – surrogate markers of subclinical atherosclerotic cardiovascular disease (ASCVD). However, treatment with levothyroxine in this population remains controversial. Methods : Electronic database search was conducted for all randomized clinical trials (RCTs) that evaluated the treatment of subclinical hypothyroidism on surrogate markers of subclinical ASCVD. The primary and secondary outcomes were the mean change of CIMT and FMD, respectively. We calculated the weighted mean differences (MDs) and 95% confidence intervals (CIs) using the inverse variance random-effects method for continuous data. Results : Seven RCTs were identified with a total of 541 patients. There were 115 males and the mean age was 54.5 ± 18.7 years with mean baseline thyroid-stimulating hormone of 6.78 ± 2.5. There were no differences between levothyroxine-treated patients and placebo with regard to CIMT differences (MD −0.02; 95% CI −0.08–0.04; P = 0.49; I 2 = 59%). However, the levothyroxine-treated group was associated with significantly increased FMD compared with placebo (MD 1.61; 95% CI 1.21–2.01; P < 0.01; I 2 = 0%). Conclusions : Among patients with subclinical hypothyroidism, levothyroxine treatment was associated with significant improvement in FMD but not CIMT. Large, adequately powered trials with long-term follow-up are needed.